The Growth of Spiritual Awareness through AA Participation: A Phenomenological Study. Issue 1 (2nd January 2020) - Vandivier, A. M.
ABSTRACT: This phenomenological study focused on the question: What is the lived-experience of the Alcoholics Anonymous (AA) Fellowship in relation to spiritual awakening for members of AA with long-term sobriety? Nine participants who had long-term sobriety, experienced a spiritual awakening, and were active in AA were interviewed, and the data gathered was analyzed through transcendental phenomenology to discover the experience of the AA Fellowship. The analysis showed multiple themes and structures that led to the creation of a synthesis of themes, explaining participants' experience of breaking down the self-view, changing life perceptions, and identifying as full Fellowship member. Limitations were considered leading to suggestions for further studies.